Study of Ozone Generation in the Bed of Heterogeneous Catalysts of Various Geometry - D.V. Maksudov; F.R. Ismagilov; I.Kh. Khairulin; S.R. Khairulin; Z.R. Ismagilov (Eurasian Chemico-Technological Journal, 2002)
An urgent worldwide problem in the field of environment protection is the development of energy saving and highly efficient technologies for removal of volatile organic compounds (VOCs) from gas emissions of large volume and emitted at rather low temperatures, such as low concentrated ventilation exhausts at room temperatures. From the other side, the efficiency of ozone-catalytic process significantly decreases due to the parallel reaction of ozone recombination to molecular oxygen. For this reason, the development of devices providing direct generation of ozone in the heterogeneous catalyst bed attracts particular interest. The application this kind of devices leads to combination of the processes of formation of highly reactive O3 molecule and oxidation of undesirable organic admixtures. In this paper the results on the development of the devices for the ozone generation directly in the bed of the catalysts of different geometry (spherical and honeycomb monolith) are presented. The experiments upon variation the electric signal frequency, flow rate have been carried out. It was shown, that developed device provides effective ozone generation within frequency range 500-1000 Hz and allow effectively combine the catalytic and electric properties and can be considered as the prototype for different appliance in environment protection.